Validity, reliability and acceptability of Professionalism Mini-Evaluation Exercise (P-MEX) for emergency medicine residency training - Amirhajlou, Leila (J Med Ethics Hist Med, 2019)
Professionalism is a core competency in the medical profession. In this paper, we aimed to confirm the validity, reliability and acceptability of the Professionalism Mini-Evaluation Exercise (P-MEX) instrument for the emergency medicine (EM) residency program. Twenty-two EM attending physicians completed 383 P-MEX forms (the Persian version) for 90 EM residents. Construct validity was assessed via structural equation modeling (SEM). The reliability coefficient was estimated by the generalizability theory, and acceptability was assessed using two researcher-made questionnaires to evaluate the perspectives of residents and assessors. There was a consensus among the participants regarding the content of P-MEX. According to the results of SEM, the first implementation of the original model was associated with a moderate fit and high item loadings. The model modified with correlated error variances for two pairs of items showed an appropriate fit. The reliability of P-MEX was 0.81 for 14 occasions. The perception survey indicated high acceptability for P-MEX from the viewpoint of the residents and increasing satisfaction with P-MEX among the assessors over time. According to the results of the research, P-MEX is a reliable, valid, and acceptable instrument for assessing professionalism in EM residents.